2013
DOI: 10.1021/ol402248s
|View full text |Cite
|
Sign up to set email alerts
|

Unconstrained Homooligomeric γ-Peptides Show High Propensity for C14 Helix Formation

Abstract: Monosubstituted γ(4)-residues (γ(4)Leu, γ(4)Ile, and γ(4)Val) form helices even in short homooligomeric sequences. C14 helix formation is established by X-ray diffraction in homooligomeric (γ)n tetra-, hexa- and decapeptide sequences demonstrating the high propensity of γ residues, with proteinogenic side chains, to adopt locally folded conformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Backbone conformational flexibilities may be restricted by multiple substitutions or by the use of cyclization restricting backbone CC torsion angles . As part of a program to investigate the intrinsic conformational preferences of β‐ and γ‐ residues derived by backbone homologation of genetically coded α amino acids (proteinogenic residues), we have been examining the solution conformations of homo‐oligomeric sequences of monosubstituted β 3 and γ 4 amino acids . In a recent report we investigated the conformation of a 9‐residue β 3 ( R )Val homo‐oligomer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Backbone conformational flexibilities may be restricted by multiple substitutions or by the use of cyclization restricting backbone CC torsion angles . As part of a program to investigate the intrinsic conformational preferences of β‐ and γ‐ residues derived by backbone homologation of genetically coded α amino acids (proteinogenic residues), we have been examining the solution conformations of homo‐oligomeric sequences of monosubstituted β 3 and γ 4 amino acids . In a recent report we investigated the conformation of a 9‐residue β 3 ( R )Val homo‐oligomer.…”
Section: Introductionmentioning
confidence: 99%
“…[6] As part of a program to investigate the intrinsic conformational preferences of band gresidues derived by backbone homologation of genetically coded a amino acids (proteinogenic residues), we have been examining the solution conformations of homo-oligomeric sequences of monosubstituted b 3 and g 4 amino acids. [12][13][14] In a recent report we investigated the conformation of a 9-residue b 3 (R) Val homo-oligomer. While the peptide existed predominantly in an aggregated form in CDCl 3 solution, addition of small amounts of the polar, hydrogen bonding solvent DMSO resulted in disaggregation, permitting complete 1 H NMR assignments and establishment of a 14-helical conformation at a solvent composition of 45% (v/v, DMSO:CDCl 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oligo α ‐Val sequences are highly insoluble in solvents like CHCl 3 at lengths 4–9 residues . The corresponding γ 4 ‐Val sequences are highly soluble and have been shown to fold into C 14 ‐helices, which are backbone expanded analogues of the α ‐peptide 3 10 (C 10 ) helix and the β‐peptide C 12 ‐helix. In sharp contrast to the γ 4 homologs, homooligomeric β 3 ‐peptides show limited solubility at the tetra to hexapeptide level in CHCl 3 but lengthening to the 9‐residue sequence enhanced solubility and facilitated formation of β ‐peptide C 14 ‐helices, with the reverse hydrogen bond directionality.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work from our laboratory has shown that homooligomeric sequence of γ 4 ‐valine have a pronounced tendency to fold into γ peptide C 14 ‐helices, which are backbone expanded analogues of the α ‐peptide 3 10 ‐helix and the β‐peptide 12‐helix . In this study, we examine the conformational possibilities of homooligomeric β 3 ‐peptides and explore the effect of inserting a single guest Aib residue into an oligo β 3 ( R )Val sequence (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…[1] Initial works focusedo np seudopeptideo ligomers [2] that comprised of as ingle type of monomer subunit,m ainly b-, g-, or d-aminoa cids, [3] and on backbones closely related to peptides,s uch as peptoids or oligoureas. [1] Initial works focusedo np seudopeptideo ligomers [2] that comprised of as ingle type of monomer subunit,m ainly b-, g-, or d-aminoa cids, [3] and on backbones closely related to peptides,s uch as peptoids or oligoureas.…”
Section: Introductionmentioning
confidence: 99%